UNDERSTANDING ATTITUDES TOWARD AND BEHAVIORS IN RESPONSE TO PRODUCT PLACEMENT: A STUDY OF LUXURY FASHION BRANDS TOWARD FEMALES IN JABODETABEK - Heidi Saputra; Ayuphita Tiara (Bina Nusantara University, 2014)
The objective of the current study is to gain a deeper understanding regarding attitudes toward and behavior in response to product placement, with additional attempts to uncover relationship between product placement in a specific luxury fashion industry and specific demographic characteristics. To collect primary data, the researcher had decided to employ a self-administered questionnaire by distributing it through printed questionnaires and online questionnaires. Peer communication and movie watching do have a significant direct linear relationship toward product placement attitudes and product placement behavior. There is no statistically significant difference between demographic information in relation to product placement attitude and behavior, except the founding that there is statistically a difference in product placement attitude related to education. There is a significant direct linear relationship between peer communication and movie watching in relation to product placement attitude and product placement behavior.